2003
DOI: 10.2320/matertrans.44.968
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulations of the Aluminium-Silicon Anomalous Eutectic Growth Based on Multiphase Field Method

Abstract: Aluminium-silicon anomalous eutectic growth has been studied numerically using a phase-field model developed to predict multiple phases. The Si phase grew very slowly in a melt of eutectic composition, but then grew substantially faster when in contact with the solidifying Al phase. The Al-liquid interface was irregular while the Si-liquid interface was flat as a consequence of the low interfacial energy between liquid and Al phases compared with that between liquid and Si. By developing a mathematical nucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…[5] This conventional dendrite fragmentation theory provides a good explanation for solid particle multiplication but cannot explain why the detached fragments would grow into globules rather than dendrites. Recent experimental studies, [19,30] supported by computer simulations, [31,32] suggest that the turbulence of high shear helps transport the accumulated solute atoms away from the solid-liquid interface and stabilizes planar growth, restraining dendrite development. Hence, the nondendritic structure is believed to be essentially a direct result of spherical growth under the forced convection.…”
Section: A Development Of Nondendritic Structuresmentioning
confidence: 99%
“…[5] This conventional dendrite fragmentation theory provides a good explanation for solid particle multiplication but cannot explain why the detached fragments would grow into globules rather than dendrites. Recent experimental studies, [19,30] supported by computer simulations, [31,32] suggest that the turbulence of high shear helps transport the accumulated solute atoms away from the solid-liquid interface and stabilizes planar growth, restraining dendrite development. Hence, the nondendritic structure is believed to be essentially a direct result of spherical growth under the forced convection.…”
Section: A Development Of Nondendritic Structuresmentioning
confidence: 99%
“…However, it is not suitable for a quaternary system. In the present simulations, one assumes that the phasefield mobility for each liquid-solid phase transitions equals 0.2 m 3 /J, which is about the same for the growth of fcc-Al and Si solid from aluminium-silicon eutectic alloys [25].…”
Section: Article In Pressmentioning
confidence: 99%
“…As the time evolves, the concentration of Si in front of the fcc-Al phase becomes progressively richer and richer, leaving a high constitutional undercooling of the Si phase. A new embryo is introduced when the solute concentration of Si is larger than 40% [25]. The new Si nuclei grow quickly along the Sirich liquid in front of the fcc-Al phase and consequently form the Si phase, which adopts a flake morphology.…”
Section: Article In Pressmentioning
confidence: 99%
“…The formation and properties of Al-Si alloys have been studied extensively by experiments [3][4][5][6][7][8][9][10]. It has been shown that the structure and properties of liquid alloys are dependent on the composition and temperature.…”
Section: Introductionmentioning
confidence: 99%